First record of a wild population of Laelia dawsonii f. dawsonii(Orchidaceae) for the state of Jalisco, Mexico - Cházaro-Basáñez, Miguel J.; Jiménez-Vázquez, Alexander; Pérez-García, Eduardo A. (Lankesteriana: International Journal on Orchidology, 2021)
The existence of a wild population of Laelia dawsonii f. dawsonii is recorded for the first time in the Mexican State of Jalisco. Laelia dawsonii has a wide geographical distribution throughout the Sierra Madre del Sur (Oaxaca, Guerrero, and Jalisco); however, the populations are very isolated, and each one has very few individuals. Until now, no wild populations of this species had been registered outside of the State of Oaxaca. The population found in Jalisco is composed of about 100 plants. Due to its horticultural importance, L. dawsonii has been frequently extracted from the field, and its Oaxacan populations have been decimated since the end of the 19th century. Currently, this species is considered endangered in Mexico. Keywords: biogeography, conservation, Laeliinae, Laelia anceps